TUGAS WEWENANG SATGAS ANTI MAFIA BOLA DALAM PENGATURAN SKOR (MATCH FIXING) DALAM PERTANDINGAN SEPAK BOLA BERDASARKAN SISTEM HUKUM PIDANA DI INDONESIA - Alexzander Rinaldy; Rasji Rasji (Jurnal Hukum Adigama, 2021)
Today's football competition has changed, because it has begun to be infiltrated by organized criminals, especially in match manipulation and match fixing. The problems faced in writing this thesis are how the authority of the soccer antimafia task force in match fixing in soccer matches based on the criminal law system in Indonesia and how to resolve crimes related to scoring in soccer matches in Indonesia. The research method used is normative legal research and empirical legal research. The results showed that the task of the Antimafia Soccer Task Force in match fixing in soccer matches based on the criminal law system in Indonesia is to minimize the improper practice of football regulation, both at the national and regional levels, to supervise the competition of League 1, League 2, and League 3, coordinating with related parties such as PSSI, Kemenpora, and Club Management, both at the national and regional levels and continue the process of handling cases of the soccer mafia scandal that has not been completed. The criminal settlement related to fixing scores in soccer matches in Indonesia is to provide fines for match fixing actors. The imposition of criminal sanctions with fines is more beneficial than imprisonment, because fines have several advantages when applied to scoring practices, among others, eliminating stigma in society, the perpetrator who is subject to a fine can stay with his family and social environment, fines do not cause the perpetrator to lose his job.